Método de coordenação e seletividade de fusíveis e religadores para redes de distribuição de energia - Rocha, Clarissa Argenti (Universidade do Vale do Rio dos Sinos, 2018)
Existing power distribution networks are increasingly required as to their reliability, energy distribution companies need to meet the criteria of individual quality indicators. To achieve the efficiency of the network, apply to it the concepts of coordination and selectivity. Looking for this concept the present work presents a method for determination of fuses and automatic circuit reclosers applied in the power distribution network to guarantee its coordination and selectivity. Through the study of the elements of protection, and the knowledge of the characteristics of the network, and how these elements should be dimensioned to be selective and coordinated, a methodology is presented for, using graphs, to determine the value of fuses and automatic circuit reclosers in a power distribution network. In the end, the methodology allows the execution of network maneuvers, and evaluates if the coordination and selectivity of the elements is still valid. For the application of this method, the IEEE network of 34 bars is adapted by adding fuses and automatic circuit recloser to allow validating the concept presented here
Keywords: Coordenação; Seletividade; Grafo; Proteção; Distribuição de energia; Coordination; Selectivity; Graph; Protection; Power distribution; ACCNPQ::Engenharias::Engenharia Elétrica